Quantitation of Nimesulide in Human Plasma by High-performance Liquid Chromatography with Ultraviolet Absorbance Detection and Its Application to a Bioequivalence Study - Rolim, Clarice Madalena Bueno; Porta, Valentina; Storpirtis, Sílvia (Arzneimittelforschung, 2007)
A rapid and simple high-performance liquid chromatography-reversed phase (HPLC-RV) method with ultraviolet detection (258 nm) was developed and validated for the quantitation of nimesulide (CAS 51803-78-2) in human plasma. After the plasma samples were extracted with 6.0 ml of dichloromethane containing the internal standard phenacetin 2 µg/ml in methanol, the analysis of the nimesulide level in the plasma samples was carried out using a reverse phase Supelcosil LC-18 (15 cm × 4.6 mm × 5 µm) column. The chromatographic separation was accomplished with an isocratic mobile phase consisting of a mixture of methanol-phosphate buffer (pH 3.5; 0.01 mol/l) (55:45, v/v). The inter-assay accuracy ranged from 103.4 to 113.2 %, while intra-day ranged from 105.6 to 117.5 %. The inter-assay precision ranged from 11.7 to 14.6 %, while intra-assay ranged from 3.2 to 9.5 %. The recovery of nimesulide was determined as part of the assay validation process and was excellent. The linearity of the nimesulide curves ranged from 0.20 to 15.0 µg/ml (y = 0.3857–0.0081, r = 0.9975).Short-term stability showed that nimesulide is stable in plasma for at least 24 h at room temperature, while long-term stability studies showed that nimesulide is stable in plasma for at least 180 days when stored at −20 °C. This validated method was successfully applied to the bioequivalence study of nimesulide in tablets in healthy volunteers.
Keywords: Anti-inflammatories, non-steroidal; CAS 51803-78-2; High-performance liquid chromatography-reversed phase; Nimesulide, bioequivalence, determination in human plasma, validation